Ownership Structure, Financial Structure and R&D Investment: Evidence from Korean Firms - CHEN, Yanghua (Institutional Knowledge at Singapore Management University, 2010)
Understanding factors that can enhance a firm‟s innovativeness is of critical concern in management research. Prior studies in strategy and financial economics have advanced our understanding of how resource allocation into innovation is shaped in a firm, mainly from the perspectives of ownership and financial structures. However, the extant literature is incomplete, because it treats ownership and financial structures as separate determinants, even though theoretical arguments and empirical evidences suggest that they are interdependent. This study investigates the determinants of firm‟s R&D investments by bridging ownership and financial structures. Ownerships held by inside and external owners are considered for ownership structure, while financial slack and leverage ratio are considered for financial structures. Exploiting simultaneous equation modeling technique and data sample of Korean firms, I found the direct and indirect effects of different types of ownership on R&D investments. Different from previous studies, this paper showed that financial factors such as financial slack and leverage ratio that were used to be considered as determinants of R&D investments are just mediators through which ownership structure affects firm‟s strategic decision indirectly.